1999
DOI: 10.1034/j.1600-0420.1999.770124.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve cysticercosis in the optic canal

Abstract: ABSTRACT. The authors present a first case of cysticercosis in the optic canal in a fifteen-year-old female patient. Cysticercosis of the optic nerve is rare. A cyst in the optic canal, beneath the sheath of the optic nerve, has never been reported. The patient presented with rapidly diminishing vision in the left eye, headache and papillitis. A magnetic resonance imaging revealed a cystic lesion at the entrance of the optic canal. Surgery performed was a transcranial orbitotomy which included deroofing of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…Subretinal cysts may produce vasculitis, chorioretinitis and macular oedema, but they rarely occur in eyelid, subconjuntiva, optic canal and lacrimal gland. 6 Orbital cystcercosis, outside the eyeball, involves extraocular muscles leading to myositis and ocular motility problems.…”
Section: Discussionmentioning
confidence: 99%
“…Subretinal cysts may produce vasculitis, chorioretinitis and macular oedema, but they rarely occur in eyelid, subconjuntiva, optic canal and lacrimal gland. 6 Orbital cystcercosis, outside the eyeball, involves extraocular muscles leading to myositis and ocular motility problems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described to present with a picture of neuroretinitis and has been previously managed with both conservative and surgical therapy. [1][2][3][4][5][6][7] The cases described in the literature have had isolated optic nerve involvement. The present case report describes a known case of neurocysticercosis with a secondary optic nerve involvement.…”
Section: Commentmentioning
confidence: 95%
“…[1][2][3][4][5][6][7] Although previous reports describe treatment with albendazole and steroids, 1,2 visual recovery in such cases has typically been limited. Surgical excision has been previously been described with total removal being achieved through a lateral orbitotomy.…”
Section: Introductionmentioning
confidence: 95%
“…On surveying the literature on myocysticercosis, we found that the commonest muscle reported to date is the medial rectus (42%), followed by superior rectus (18%), lateral rectus (15%), inferior rectus (13%), superior oblique (5%), levator palpebral superioris (5%) and inferior oblique (1%) 6,23,26,28,34−41,43,62−65 . The subconjunctival space is another common site, 6,21,24,33,38 followed by the eyelid, 6,12,21,22,27,40,66,67 optic nerve, 5−11 retro‐orbital space 6,12,28,35 and lacrimal gland 12,29 . In all cases of eyelid cysticercosis so far recorded, the cyst was found to be lodged in the subcutaneous tissue, except in one case, where it lodged in the orbicularis oculi muscle 12 .…”
Section: Aetiology and Life Cycle Of Taenia Soliummentioning
confidence: 99%
“…Following these reports, curiosity about ophthalmic cysticercosis increased, leading to the discovery of Cysticercus at different locations within the eyeball, orbit and adnexa. The first case of optic nerve cysticercosis was published in 1962, 5 following which six more cases of optic nerve cysticercosis have been reported in world literature 6−11 . Lodgement of C. cellulosae in the lacrimal gland and orbicularis oculi muscle was first reported after histopathological confirmation in 1979 12 …”
Section: Introductionmentioning
confidence: 99%